Opening the policy window for sugar-sweetened beverage tax: lesson learned from Mexico - Sarah Maria Saragih (Berita Kedokteran Masyarakat (BKM), 2019)
Purpose: Worldwide, a model showed that 184000 death/year attributable to sugar-sweetened beverage (SSB) consumption. Accordingly, as the country with the largest absolute death from SSB, Mexico implements SSB tax measure which not successfully applied by several countries. Therefore, the objective of this research is to identify lesson learned from Mexican SSB tax enforcement and to analyze policy window of SSB tax implementation in Indonesia. Methods: Data collection was conducted through literature and media review with applied time window for specific topic. The author analyzes policy process with Walt and Gilson policy triangle theory and identifies policy window with multiple streams Kingdon theory. Result: Mexican SSB tax successfully reduced its consumption by 5.5 %, which shown in the decrease of 7.3% in per capita sales and increase of purchase non-taxed beverages (36mL/capita/day) in 2014. Findings show, continuous advocacy conducted by nutritional health alliance (non-governmental organization like PAHO/WHO, civil society organizations-CSO, nonprofit and grassroots organization) with financial assistance from Bloomberg philanthropy institution and scientific publication issued by academic communities, also political interest contributed to the success of SSB tax enforcement. In the context of Indonesia, the rising of obesity and overweight prevalence as well as increasing health expenditure on metabolic related diseases troubled government which resulted in political commitment in 2015-2019. SSB tax implementation can be the solution to crack down its consumption. While the executive and legislative election in 2019 can be benefited to advance passing SSB tax. A coupled of problem, policy, and politic streams will create policy window of SSB tax. Conclusion: As with Mexico, Indonesia will require broad-based advocacy, key stakeholders involvement, and political interest to success the tax enforcement utilizing today’s policy window. Further research required to explore the feasibility of SSB tax implementation in Indonesia.